Altered muscle satellite cell activation following 16 wk of resistance training in young men - Nederveen, Joshua P. (Am J Physiol Regul Integr Comp Physiol, 2017)
Skeletal muscle satellite cells (SC) play an important role in muscle adaptation. In untrained individuals, SC content and activation status have been observed to increase in response to a single bout of exercise. Muscle fiber characteristics change considerably when resistance exercise is performed chronically, but whether training status affects the activity of SC in response to a single bout of exercise remains unknown. We examined the changes in SC content and activation status following a single bout of resistance exercise, before and following a 16-wk progressive resistance training (RT) program in 14 young (25 ± 3 yr) men. Before and after RT, percutaneous biopsies from the vastus lateralis muscle were taken before a single bout of resistance exercise and after 24 and 72 h of postexercise recovery. Muscle fiber size, capillarization, and SC response were determined by immunohistochemistry. Following RT, there was a greater activation of SC after 24 h in response to a single bout of resistance exercise (Pre, 1.4 ± 0.3; 24 h, 3.1 ± 0.3 Pax7(+)/MyoD(+) cells per 100 fibers) compared with before RT (Pre, 1.4 ± 0.3; 24 h, 2.2 ± 0.3 Pax7(+)/MyoD(+) cells per 100 fibers, P < 0.05); no difference was observed 72 h postexercise. Following 16 wk of RT, MyoD mRNA expression increased from basal to 24 h after the single bout of exercise (P < 0.05); this change was not observed before training. Individual capillary-to-fiber ratio (C/Fi) increased in both type I (1.8 ± 0.3 to 2.0 ± 0.3 C/Fi, P < 0.05) and type II (1.7 ± 0.3 to 2.2 ± 0.3 C/Fi, P < 0.05) fibers in response to RT. After RT, enhanced activation of SC in response to resistance exercise is accompanied by increases in muscle fiber capillarization.